2014
DOI: 10.1186/bf03352410
|View full text |Cite
|
Sign up to set email alerts
|

Local time dependence of the equatorial counter electrojet effect in a narrow longitudinal belt

Abstract: Irregular occurrence characteristics of the equatorial counter electrojet phenomena at different longitudinal zones are investigated using the magnetic data of the horizontal component 'H ' at the two equatorial stations Trivandrum and Addis Ababa, separated in longitude by about 40• . The limited longitudinal extent of the counter electrojet (CEJ) events are examined on the basis of the occurrence of the phenomenon at different local time intervals. Importance of the solar semi diurnal tides in modifying the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 26 publications
4
24
0
Order By: Relevance
“…The noticeable geomagnetically quiet period, usually preceding the high‐speed stream‐generated storms, produces an opportunity to investigate the meteorological influences on the ionosphere since the magnetospheric energy inputs are of minimum in this interval. For the periods of 3–4 January 2008, the weaker daytime EIA and not well‐developed eastward electrojet as observed inFigures 2a and 2d are a commonplace occurrence [e.g., Alex and Mukherjee , 2001; Stening , 1995]. Day‐to‐day variations in eastward equatorial electrojet (EEJ) and counter electrojet (CEJ) are related to various tidal modes and zonal winds of varying magnitude [ Forbes and Lindzen , 1976; Somayajulu et al , 1993; Stening , 1995].…”
Section: Observations and Interpretationmentioning
confidence: 99%
“…The noticeable geomagnetically quiet period, usually preceding the high‐speed stream‐generated storms, produces an opportunity to investigate the meteorological influences on the ionosphere since the magnetospheric energy inputs are of minimum in this interval. For the periods of 3–4 January 2008, the weaker daytime EIA and not well‐developed eastward electrojet as observed inFigures 2a and 2d are a commonplace occurrence [e.g., Alex and Mukherjee , 2001; Stening , 1995]. Day‐to‐day variations in eastward equatorial electrojet (EEJ) and counter electrojet (CEJ) are related to various tidal modes and zonal winds of varying magnitude [ Forbes and Lindzen , 1976; Somayajulu et al , 1993; Stening , 1995].…”
Section: Observations and Interpretationmentioning
confidence: 99%
“…The seasonal variability (equinox to local summer) in occurrence of CEJ events is observed to be much larger (5–35%) compared to that (32–35%) reported from Addis Ababa (geographic: latitude, 9°N; longitude, 38.8°E; dip: 1°S) [ Mayaud , 1977]. It may be due to limited longitudinal confinement nature of CEJ events – which is attributed to the local wind shear modifying the EEJ fields especially during noontime hours [ Alex and Mukherjee , 2001]. The later occurrence of initiation time during J months is suggested to be related to the northward shifted position of the Sun with respect to the magnetic equator [ Rastogi , 1974].…”
Section: Resultsmentioning
confidence: 99%
“…Although a large number of investigations on theoretical as well as experimental grounds are conducted to find and explain the characteristics of CEJ event, its causes and effects on the equatorial and off‐equatorial ionosphere [ Rajaram and Rastogi , 1974; Deshpande et al , 1977; Raghavarao and Anandarao , 1987; Alex and Mukherjee , 2001; Devasia et al , 2006], the effect of CEJ on diurnal variation of TEC near the anomaly crest region is yet to be fully explored. TEC is an important parameter to describe the state of ionosphere and significant for time delay/range error problems involving global positioning system (GPS) navigation.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, large depression of Δ H (CEJ signatures) predominantly in the morning hours is also expected to contribute to negative E × B values derived from equation . Possible sources of CEJ have been suggested to be gravity waves associated with vertical local winds (e.g., Raghavarao & Anandarao, ) and solar tidal modes (e.g., Alex & Mukherjee, ; Gurubaran, ). From Figure c it can be observed that there is some correlation between F 10.7 and ionospheric vertical drifts, although the investigated period has a significant amount of missing E × B drift data.…”
Section: Methodsmentioning
confidence: 99%